Method of pedicle division during laparoscopic right hemicolectomy affects lymph node yield and short‐term outcomes. Issue 10 (27th April 2018) - Pal, Atanu; Stearns, Adam T.; Kapur, Sandeep; Speakman, Christopher T. M.; Wharton, Richard Q.; Shaikh, Irshad; Hernon, James M.
Abstract : Background: Several ways of performing laparoscopic right hemicolectomy (RHC) have evolved. The vascular pedicle can be divided into extracorporeal (RHC‐EC) or intracorporeal (RHC‐IC). It is not known whether vessel ligation during RHC‐EC is as central as during RHC‐IC. We compare these approaches in terms of pathological and short‐term clinical outcomes. Methods: Patients undergoing elective laparoscopic RHC in a single centre (July 2013–September 2016) were identified. Data collection included operative details, length of stay, complications, specimen parameters including number and involvement of lymph nodes and recurrence. Results: One hundred and sixty‐nine patients were included (94 RHC‐IC, 75 RHC‐EC). For caecal and ascending colon cancers, mesocolic width was greater after RHC‐IC than RHC‐EC (7.9 cm versus 6.6 cm, P  < 0.05), as was lymph node yield (19.5 versus 17.3, P  < 0.05). There was no significant difference in length of colon resected, distal resection margin, number of positive nodes, proportion of node‐positive tumours and R1 rate. Operative duration was higher for RHC‐IC (163 min versus 91 min, P  < 0.001), as was incidence of ileus (35% versus 15%, P  < 0.05). Length of stay also tended to be higher (7.4 days versus 6.0 days, P  = 0.19). There was no difference in disease recurrence (follow‐up 12 months). Body mass index was positively correlated with lymph node yield for RHC‐EC, but not for RHC‐IC. Conclusion: Lymph node yield after laparoscopic RHC is adequate, whether the vascular pedicle is taken intracorporeal or extracorporeal, supporting the use of both approaches. RHC‐IC yields more lymph nodes and greater mesocolic width, but involves a longer operation and higher incidence of ileus.